Bone marrow mesenchymal stromal cell-derived extracellular matrix displays altered glycosaminoglycan structure and impaired functionality in Myelodysplastic Syndromes - Bains, Amanpreet Kaur; Behrens Wu, Lena; Rivière, Jennifer; Rother, Sandra; Magno, Valentina; Friedrichs, Jens; Werner, Carsten; Bornhäuser, Martin; Götze, Katharina S.; Cross, Michael; Platzbecker, Uwe; Wobus, Manja (Frontiers in Oncology, 2022)
Myelodysplastic syndromes (MDS) comprise a heterogeneous group of hematologic malignancies characterized by clonal hematopoiesis, one or more cytopenias such as anemia, neutropenia, or thrombocytopenia, abnormal cellular maturation, and a high risk of progression to acute myeloid leukemia. The bone marrow microenvironment (BMME) in general and mesenchymal stromal cells (MSCs) in particular contribute to both the initiation and progression of MDS. However, little is known about the role of MSC-derived extracellular matrix (ECM) in this context. Therefore, we performed a comparative analysis of in vitro deposited MSC-derived ECM of different MDS subtypes and healthy controls. Atomic force microscopy analyses demonstrated that MDS ECM was significantly thicker and more compliant than those from healthy MSCs. Scanning electron microscopy showed a dense meshwork of ﬁbrillar bundles connected by numerous smaller structures that span the distance between ﬁbers in MDS ECM. Glycosaminoglycan (GAG) structures were detectable at high abundance in MDS ECM as white, sponge-like arrays on top of the ﬁbrillar network. Quantification by Blyscan assay confirmed these observations, with higher concentrations of sulfated GAGs in the ECM of MDS. Fluorescent lectin staining with wheat germ agglutinin and peanut agglutinin demonstrated increased deposition of N-acetyl-glucosamine GAGs (hyaluronan (HA) and heparan sulfate) in low risk (LR) MDS ECM. Differential expression of N-acetyl-galactosamine GAGs (chondroitin sulfate, dermatan sulfate) was observed between LR- and high risk (HR)-MDS. Moreover, increased amounts of HA in the matrix of MSCs from LR-MDS patients were found to correlate with enhanced HA synthase 1 mRNA expression in these cells. Stimulation of mononuclear cells from healthy donors with low molecular weight HA resulted in an increased expression of various pro-inflammatory cytokines suggesting a contribution of the ECM to the inflammatory BMME typical of LR-MDS. CD34+ HSPCs displayed an impaired differentiation potential after cultivation on MDS ECM as well as modified morphology accompanied by decreased integrin expression which mediate cell-matrix interaction. In summary, we provide evidence for structural alterations of the MSC-derived ECM in both LR- and HR-MDS. GAGs may play an important role in this remodeling processes during the malignant transformation which leads to the observed disturbance in the support of normal hematopoiesis.